Case Report: Cervical carbon fiber-reinforced PEEK pedicle screw fixation with 3D custom-made template guides for spinal oncology surgery - Cofano, Fabio; Marengo, Nicola; Colonna, Stefano; Rizzo, Francesca; Lacatena, Filippo; Garbossa, Diego (Frontiers in Surgery, 2026)
Cervical spine fixation in oncological and tumor-like conditions poses unique mechanical and radiological challenges. The choice of implant material is crucial to ensure optimal biomechanical stability and minimize imaging artifacts that may hinder adjuvant radiotherapy. While traditional titanium constructs provide reliable mechanical performance, they generate significant postoperative artifacts. Carbon fiber–reinforced PEEK (CFR-PEEK) implants offer comparable biomechanical strength with markedly reduced imaging interference, facilitating radiotherapy planning. However, their application in the cervical spine remains extremely limited due to narrow anatomical corridors. This technical note reports the first use of CFR-PEEK cervical pedicle screws (CPS) guided by patient-specific 3D-printed templates in the treatment of an aggressive vertebral hemangioma. The study demonstrates the technical feasibility and clinical applicability of CFR-PEEK screws with customized 3D guides for posterior cervical fixation in complex oncologic cases.